China : land of the emperor's Great Wall - Osborne, Mary Pope (Magic tree house fact tracker.)
Track the facts with Jack and Annie! When Jack and Annie came back from their adventure in Magic Tree House(R) #14: "Day of the Dragon King, " they had lots of questions. Who was the Dragon King? How did he build the Great Wall? What is Chinese New Year? What are some other Chinese traditions? Find out the answers to these questions and more as Jack and Annie track the facts about Chinese history and culture.